Speech Function of Anies Baswedan in His Governor Inaugural Ceremony - Ahmad Rifa'i Ritonga; Sumarsih . .; Anni Holila Pulungan (Universitas Negeri Medan, 2021)
ABSTRACTLanguage forms a dialogue that becomes a very important matter in communicating. Dialogue is related with speech function. Halliday (1994) suggests that dialogue is a process of exchange involving two variables; those are: (1) a commodity to be exchanged; either information or good and service and (2) roles associated with exchange relations; either giving or demanding. Halliday (1994) states that there are four basic types of speech functions; those are: offer, statement, command, and question. This study tries to analyze the speech function of used by Anies Baswedan in his speech when he was ceremonially approved the governor of Jakarta in the Period of 2017-2022. Based on the data analysis, it was got that there are 75 independent clauses of which speech functions are statement, and there are 7 independent clauses of which speech functions are command. The speech functions of statement are in marked and unmarked mood, while the command ones are in unmarked mood. The types of speech function found in the speech are correlated with the function found in the speech are correlated with the function and the goal of the speech. Keywords: Speech Function, Speech, Governor, Inaugural Ceremony.